PENGEMBANGAN PERANGKAT PEMBELAJARAN MODEL SSCS DENGAN PENDEKATAN RME DAN PENGARUHNYA TERHADAP KEMAMPUAN BERPIKIR KOMPUTASIONAL - Fathimah Azzahraail Batul; Didik Sugeng Pambudi; Antonius Cahya Prihandoko (UNIVERSITAS MUHAMMADIYAH METRO, 2022)
This study aims to develop a mathematics learning tool consisting of a Learning Implementation Plan (RPP), Student Worksheet (LKS), and a Computational Thinking Test (CT Test) using the Search, Solve, Create, and Share (SSCS) learning model with a Realistic approach. Mathematics Education (RME) which is valid, practical and effective and examines its effect on the computational thinking ability of junior high school students. This research combines development research (R&D) and experimental research. Data collection techniques in this study used interviews, observation of student activities, observation of the implementation of learning devices, student response questionnaires, and learning outcomes tests in the form of CT tests. The results showed that the learning tools met the criteria of being valid, practical, and effective. The validity coefficients for lesson plans, worksheets, and CT tests were 3.80, respectively; 3.80; and 3.81. The value of practicality seen from the results of observations of the implementation of learning devices is in the very practical category with a percentage of 98%. The value of the effectiveness of learning tools shows that 92% of students are active, 98% of students respond positively to learning, and 77% of students complete learning. Based on the t-test on the results of experimental research, it was found that the SSCS model learning device with the RME approach had a significant effect on students' computational thinking abilities.